Growth of Jatropha curcas L. seedlings in copper-contaminated soils amended with compost and Trichoderma pseudokoningii Rifai - Fontanilla, Cyreene S.; Cuevas, Virginia C. (2010)
A pot experiment was conducted to determine the growth and copper accumulation of Jatropha curcas L. seedlings in soils contaminated with high (212 ppm) and low (42 ppm) levels of Cu. The soils were collected 200 m and 10 km, respectively, from an abandoned Cu mine site in Mogpog, Marinduque, Philippines. The soils were amended with 0.025% Trichoderma pseudokoningii R., 20% compost, and 20% compost + 0.025% T. pseudokoningii R. (w/w), and analyzed for pH and Cu content before and after the experiment. Cu content of the various plant organs was also analyzed after 6.5 mo of growth. J. curcas seedlings grown with 20% compost were able to decontaminate the soil to within-normal levels of Cu (30 ppm) in uncontaminated soil, reducing mean Cu concentrations from 169.6 to 28 ppm in high-Cu-contaminated samples and from 33.6 to 4.0 ppm in low-Cu-contaminated samples. T. pseudokoningii inoculation had no effect on the seedlings. In the 212 ppm Cu-contaminated soil, seedlings died after 1 mo in the control and in the T. pseudokoningii treatment (with or without compost). In the 42 ppm Cu-contaminated soil, seedlings in the control and in the fungal-amended soil performed very poorly compared with those grown in soil amended with compost. Growth improvement with compost was due to increased soil pH and reduction of Cu content in the potting media. The latter effect was probably due to the ability of organic matter in compost to form complexes with heavy metals. The seedlings accumulated a total of 356 ppm and 46.5 ppm Cu in the high-and the low-contamination potting media, respectively. The roots accumulated more than twice the Cu level absorbed by the other plant organs. Results of this study may help in the formulation of a strategy for rehabilitation of areas covered with copper-rich mine tailings in Mogpog, Marinduque and other areas of the country with a similar problem.
Keywords: Phytoremediation